COMPARATIVE ANALYSIS OF GLOBAL DEVELOPMENT MODELS: GENERALISATION OF FOREIGN EXPERIENCE (Comparative Professional Pedagogy, 2025)
The article provides a comparative analysis of global development models. The European experience, as well as the experience of the United States and Japan, is valuable for the study. The models of these countries were used for comparative analysis in this publication. It is determined that the adaptation of the best international practices to the conditions of Ukraine is worthy of attention, since the search for the latest development models is focused on the transformation of the individual. It is stated that in order to attract positive experience, the conditions for the internal motivation of a teacher must be created by a modern manager of an educational institution. It is noted that the competence of the administrator of an educational institution, the effectiveness of his/her management decisions determine the quality of management to improve the creative activity and motivation of the school team, the ultimate goal of which is the quality of educational services.  The importance of providing quality education through an innovative approach to management is emphasised. The role of the manager-leader in the dynamics of personal transformation is emphasised. Particular attention is paid to the approaches and strategies used for their professional growth, competitiveness and image of the educational institution. Its image determines the direct connection between the organisation, which provides quality educational services, and all participants of the educational process. Since they are related to solving the tasks, determining the contingent of future knowledge seekers, attention is focused on certain components of the manager's competence, which is responsible for human capital, development of creative potential (CP) of each individual, in particular the level of emotional intelligence (EI). The recommendations for the implementation of the model of managing teachers' creative potential development (MTCPD) in educational institutions are separately outlined.The article is a contribution to the study of the process of managing the development of teachers' creative potential by revising traditional approaches to determining the level of their CP. Thus, the successful implementation of the URTPD model will help to solve educational problems and make competent decisions.
Keywords: innovative models of development; management methods; model of managing teachers' creative potential development; andragogical approach; qualimetric approach; manager-leader; professional competence